A Semiotic Study of Barista Personal Branding: Mikael Jasin on Instagram - Irfani Zukhrufillah, Irfani; Rahayu, Fitria Furi (International Journal of Multidisciplinary Applied and Science Research, 2025)
A barista is someone skilled in serving coffee; the barista world has given rise to new trends such as brewing and artisan coffee. Personal branding has become an important factor for baristas to create a self-image in the eyes of the general public. This research aims to understand the personal branding carried out by Mikael Jasin on Instagram. The research method is descriptive qualitative with an approach based on Charles Sanders Peirce's semiotic theory, comprising icon, index, and symbol. The results show that Mikael Jasin engages in a form of personal branding by displaying photos and videos featuring Icons such as coffee machines, espresso cups, and grinders. Indexes include captions and hashtags used in posts. The Symbol of the apron represents the identity of a barista.